Poor sleep quality and associated factors among adult chronic kidney disease patients - Gela, Yibeltal Yismaw; Limenh, Liknaw Workie; Simegn, Wudneh; Ayenew, Wondim; Chanie, Gashaw Sisay; Seid, Abdulwase Mohammed; Beyna, Alemante Tafese; Esubalew, Dereje; Mitku, Melese Legesse; Mengesha, Assefa Kebad; Melese, Mihret (Frontiers in Medicine, 2024)
Background: Poor sleep quality is a common concern in chronic kidney disease (CKD) patients, which can accelerate the progression of chronic renal disease and negatively impact their health-related quality of life, potentially leading to greater morbidity and mortality rates. It can also have an effect on the immune system, cognitive function, and emotional well-being of CKD patients. Furthermore, poor sleep quality may contribute to drug noncompliance and decreased participation in the entire treatment plan.Nonetheless, no research has been undertaken in Ethiopia on the prevalence of poor sleep quality and its associated factors among CKD patients.